Analisis Teoritis tentang Pembelajaran Berbasis Kebutuhan Anak Usia Dini di Kelas Awal MI/SD - Liandy, Septian (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to analyze relevant learning theories and develop a learning model based on the needs of early childhood education in the early grades of MI/SD. This research is a library research, with the subjects being various relevant learning theories and the object being the application of these theories in the context of early childhood education. Data collection was carried out through literature studies from various academic sources, while data analysis was conducted using thematic analysis of existing learning theories. The results show that theories such as Piaget, Vygotsky, Bandura, as well as connectionism and behaviorist approaches play a significant role in designing learning that aligns with the needs of early childhood learners. This study concludes that learning based on these theories can enhance cognitive, social, emotional, and physical development in children. The developed learning model is expected to be implemented in early-grade MI/SD classrooms to support more effective and contextual early childhood education.